Distribuição espacial de insetos predadores em riachos da região norte da Serra do Mar, Estado de São Paulo - Vilardi, Gabriel Cestari (Universidade Federal de São Carlos, 2010)
This study aimed at determining whether environmental factors as vegetation, environmental integrity, water flow, water velocity and physical and chemical characteristics of the water (pH, dissolved oxygen, temperature and conductivity) can predict the richness, abundance and faunal composition of predator insects which live in bedrock of Atlantic Rainforest streams. The collecting of fauna has been carried out in streams located in the Núcleos Santa Virgínia and Cunha-Indaiá, both located in the Parque Estadual Serra do Mar, São Paulo state, in October 2006 and October and November 2007. In each stream was selected a stretch of about 50 meters. The fauna associated with 25 cobble type rocks was collected with the aid of a hand net with a mesh of 0.25 millimeters. Were collected 779 individuals in 17 taxa. The most abundant taxa were Anacroneuria, Limnocoris, Neotrephes and Argia. The Detrended Correspondence Analysis (DCA) showed a cluster of sampling points according to the scale of the vegetation cover. The graphic representation of similarity matrix Morisita- Horn by UPGMA revealed the formation of clusters consisting of the fauna collected at sites with different water flows, but with similar vegetation cover. The Mantel Test showed a significant relationship of the predatory insects fauna in the vegetation cover (r = -0.189, p = 0.017 for 5000 permutations) and water velocity (p = 0.05 and r = -0.3 for 5000 permutations). The partial coefficients estimated from multiple linear regression showed that the flow has significant influence on the analyzed entomofauna.
Keywords: Interrelação específica de organismo e meio ambiente; Ação antrópica; Fauna de córregos; Macroinvertebrados aquáticos; Distribuição espacial; Anthropic action; Aquatic macroinvertebrates; Fauna of streams; Spatial distribution; CIENCIAS BIOLOGICAS::ECOLOGIA